Loss of p53 Expression in Gastric Epithelial Cells of Helicobacter pylori-Infected Jordanian Patients - Mohammad A. Abu-Lubad; Ghada F. Helaly; Weliam J. Haddadin; Dua’a A. K. Jarajreh; Amin A. Aqel; Munir A. Al-Zeer (International Journal of Microbiology)
Background. Around half of the global population is chronically infected with the stomach bacterium Helicobacter pylori, making it one of the most common chronic infections worldwide. H. pylori induces the production of reactive oxygen species, DNA damage, and accelerates the degradation of the tumor suppressor protein p53, which may lead to cancer development. In this study, we investigated the relationship between H. pylori infection and the expression of p53 in gastric mucosa in a group of patients from Jordan. Methods. In this retrospective case-control study, the epithelium of gastric glands in subjects chronically infected with H. pylori was examined for the expression of p53. Paraffin-embedded gastric biopsy samples from the archives for 50 Jordanian patients diagnosed with chronic H. pylori infection and 25 samples free of H. pylori infection and any other gastric abnormalities were selected. Samples were analyzed for the presence of H. pylori as well as p53 expression levels in the mucosa and submucosa by immunohistochemical analyses and Western blotting. Results. H. pylori was detected in the gastric tissues of infected individuals (n = 50); whereas, no H. pylori infection was detected in uninfected healthy individuals (n = 25) using immunohistochemistry. In contrast to the noninfected samples of gastric mucosa, no nuclear p53 expression was detected in the infected samples using immunohistochemistry. In addition, the levels of p53 in H. pylori-positive samples detected by Western blotting were significantly lower than those in the negative individuals. Conclusion. Our data reveal that p53 protein expression decreased in gastric mucosa of patients infected with H. pylori. The loss of this tumor suppressor may play a role in the increased risk for tumor initiation associated with H. pylori carriage.